P5. Hands-on radionuclide activity meter (dose calibrator) training at NMISA. (September 2016) - van Rooy, M.; Simpson, B.; Lubbe, J.; van Staden, M.
Abstract : Introduction: Radionuclide activity meters (commonly known as dose calibrators) are used to accurately measure the activity of radionuclide solutions used in nuclear medicine. Medical physicists are required to frequently check the accuracy of hospital dose calibrators by measuring calibration sources, the results of which must be within 10% accuracy to be deemed acceptable. Administering inappropriate amounts of radioactivity to a patient can result in ineffective treatment. Materials and methods: The National Metrology Institute of South Africa (NMISA) is offering training to honours and fourth year medical physics students through a project on dose calibrator measurements. The objective is to identify and calculate the activity and corresponding uncertainties of a mixture of three unknown gamma emitting radionuclides contained in a solution. The student will be required to identify each radionuclide after measuring a spectrum with a high purity germanium (HPGe) detector. Using the NMISA ionisation chamber and electrometer, the student will be required to measure the current produced by gamma radiation emitted from a standard source of each of the identified radionuclides and calculate the corresponding calibration factors, with uncertainties. The student will be required to measure the total current produced by the three radionuclides over a period of one to two months and extract the activity of each radionuclide by deconvolution and using the calibration factors determined. An uncertainty budget will be compiled for each radionuclide. Results: The project feasibility has been demonstrated through simulation of the current produced by a mixture of Ga-67, I-131 and Fe-59 over a period of one month. Statistical variation was included by altering the simulated total current appropriately, and an uncertainty on each data point was added, both procedures following a Gaussian distribution between 0 and 0.5%. The extracted activities showed agreement within 3 standard deviations, with 3% discrepancy from the expected values. Conclusion: Students will receive relevant hands-on training, a requirement to become a medical physicist.